Results on Chatterjea’s Contraction in b-Metric Space (Patan Prospective Journal, 2024)
In 1922, Polish mathematician S. Banach introduced contraction conditions in metric space and confirmed that every contraction mapping in a complete metric space gives a unique fixed point. In 1968, R. Kannan generalized Banach contraction, and S. K. Chatterjea modified the Kannan contraction in 1972.This paper aims to show that any contractive condition need not be a weak contraction mapping in b-metric space.